Who can hold the sea the U.S. Navy in the Cold War, 1945-1960 - Hornfischer, James D. (Bantam Books, 2022)
"A close-up, action-filled narrative about the crucial role the U.S. Navy played in the early years of the Cold War, from the New York Times bestselling author of The Fleet at Flood Tide This landmark account of the U.S. Navy in the Cold War, Who Can Hold the Sea, combines narrative history with scenes of stirring adventure on--and under--the high seas. In 1945, at the end of World War II, the victorious Navy sends its sailors home and decommissions most of its warships. But this peaceful interlude is short-lived, as Stalin, America's former ally, makes aggressive moves in Europe and the Far East. Winston Churchill crystallizes the growing Communist threat by declaring the existence of "the Iron Curtain," and the Truman Doctrine is set up to contain Communism by establishing U.S. military bases throughout the world. Set against this background of increasing Cold War hostility, Who Can Hold the Sea paints the dramatic rise of the Navy's crucial postwar role in a series of exciting episodes: the tests of A-bombs dropped on warships at Bikini Island the growing science of undersea warfare and invention of sonar the Korean War as a deadly test of naval superiority the growth of the modern Navy with its dramatic game-changers: cruisers fitted with surface-to-air missiles, and the invention of the nuclear submarine lessons learned from the dramatic sinking of the submarine USS Cochino in the Norwegian Sea the USS Nautilus's dangerous, first-ever cruise underneath the North Pole As in all of Hornfischer's work, the events unfold in riveting--and often surprising--detail. The story of the Cold War at sea is ultimately the story of America's victorious contest to protect the free world"--